1995
DOI: 10.1007/bf00011360
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and nitrogen fertilization of a Norway spruce forest-effects on needle concentrations and acid phosphatase activity in the humus layer

Abstract: Increased atmospheric deposition of N might eventually lead to P deficiency. The relation between needle P concentration and acid phosphatase activity in the humus layer was studied during 1990-93 in a Norway spruce stand where the water and N and P supplies had been experimentally manipulated since 1988. Treatments included control (C), yearly application of ammonium sulphate (NS), N-free fertilizer (V), granulated wood ash (A), irrigation (I), drought (D) and water plus nutrients in an "optimum" combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Therefore, since the decay rate in Sphagnum litter increases with its N concentration (Limpens and Berendse 2003), an overall increase in the litter decay rates might be supposed to have taken place at these sites. Fertilization with N has also been shown to increase the activity of extracellular acid phosphatase in various forest soils (Clarholm and Rosengren‐Brinck 1995, Treseder and Vitousek 2001). In the same way addition of extra N to peat soils has been shown to increase both phosphatase activity and extractable P in the treated soil (Williams and Silcock 1997, 2001, Kang and Freeman 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, since the decay rate in Sphagnum litter increases with its N concentration (Limpens and Berendse 2003), an overall increase in the litter decay rates might be supposed to have taken place at these sites. Fertilization with N has also been shown to increase the activity of extracellular acid phosphatase in various forest soils (Clarholm and Rosengren‐Brinck 1995, Treseder and Vitousek 2001). In the same way addition of extra N to peat soils has been shown to increase both phosphatase activity and extractable P in the treated soil (Williams and Silcock 1997, 2001, Kang and Freeman 1999).…”
Section: Discussionmentioning
confidence: 99%
“…1), although few studies have examined that possibility. Clarholm and Rosengren-Brinck (1995) found that N fertilization increased phosphatase activity in soils under a Norway spruce forest, although free-living soil microbes could have contributed to phosphatase production. Numerous studies have reported reductions in extracellular acid phosphatase activity per unit root in response to increased P availability ( Fig.…”
Section: Introductionmentioning
confidence: 92%
“…The measured effect on foliar concentrations, however, depends on degree of limitation on needle growth and time span between release of the water stress and the sampling. Clarholm and Rosengren-Brinck (1995), for example, reported about equal foliar concentrations of both N and P in current needles for each of the 3 years 1990 -1992 in Skogaby on the south-west coast of Sweden, even though the trees suffered from a serious drought from about 10 May to 15 July 1992. The reason for this is probably, as already discussed, that the foliar concentration of nutrients in late autumn does not necessarily reflect the levels at the time when the drought occurred.…”
Section: Interactions Between Shoot Elongation and Droughtmentioning
confidence: 96%